EXTRACT AND FRACTIONS EXPLORATION OF DAYAK ONION (Eleutherine America-na Merr.) WITH ANTIOXIDANTS POTENTIAL USING GC-MS and FTIR METHODS - Elisa, Novi; Advistasari, Yustisia Dian; Lepangkari, Jaka Seprianto; Hidayatullah, Muhammad Haqqi (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2025)
Free radicals can cause various diseases in the body if not treated immediately. Large levels of free radicals may trigger damage to normally functioning tissues, lipid layers, blood vessels, DNA synthesis disturbances, and even destruction of cells. The objective is to evaluate the antioxidants potential of dayak onion extract and fractions. FTIR spectrophotometers, gas chromatography-mass spectrometry (GC-MS) and an antioxidants multimode reader are some of the research methods. The outcomes of this research are identifying plants that showed the dayak onion extract of the species Eleutherine Americana Merr. It contains compounds such as flavonoids, alkaloids, tannins, and saponins. In addition, the components found in the extract, water fraction, ethyl acetate fraction, and n-hexane fraction are octadecanoic acid 298 m/z, 9-octadecanoic acid 282 m/z, undecanoic acid 214 m/z, hexadecanoic acid 368 m/z, and nonadecanoic acid 326 m/z. Therefore, the antioxidants test using the DPPH method showed that the best IC50 value is for ethyl acetate with IC50 20.56 ppm.